Echo and the Ecumene: Grasping the Estonian National Museum. Issue 1 (1st March 2022) - Leete, Art; Laviolette, Patrick
Abstract: A duo-biographical recollection of an encounter, this article comprises a dialogue between the authors. On the one hand, it is about a shared moment – a tandem 'go-along' tour of the Echo of the Urals exhibition in the Estonian National Museum. On the other, it is about certain similarities and differences in the disciplinary approaches to curating as well as to spectating an 'inter-national' museum space in Estonia's second-largest city, Tartu.